The Strange Tale of Tom Cassidy and Catherine Rose, or, Free Love, Heterosexuality, and the One Big Union - McCallum, Todd (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1998)
AbstractWhen Tom Cassidy and Catherine Rose were purged from the One Big Union (OBU) in October 1923 for their illicit sexual relationship, it unleashed an intense and at times dramatic series of confrontations lasting more than six months in which members said to advocate the ideals of “free love” became the greatest threat to the union's existence. Remarkably, these debates at dozens of union meetings occurred without any public reference to sex. Instead, OBU executive members contained the sexual content of Cassidy's and Rose's affair by posing the question of their relationship in terms of a value judgement about what would hinder the progress of the union. To talk of sex, they argued, would enable a sexual Red Scare at the hands of the bourgeois press. The OBU would be destroyed in the ensuing panic over charges of “free love” and the working-class movement for liberation would be undermined. But underneath their concern to protect the union's reputation lay patriarchal assumptions about heterosexuality, both as sexual practice and family structure, to explain the union's existence, its organizational tactics, and their dream of a better future. Thus, it was not so much that the OBU Executive refused to challenge conservative sexual values to protect the union, but that they promoted these values.